Light activated shape memory polymers and composites: A review. (5th August 2020) - Herath, Madhubhashitha; Epaarachchi, Jayantha; Islam, Mainul; Fang, Liang; Leng, Jinsong
Graphical abstract: Highlights: Photoresponsive and photothermal mechanisms form light induced shape memory effect. Light enables selective, sequential, reversible, multiple and remote activations. Optical technologies aid to disperse light onto surfaces and into materials. Light activation advances biomedical, aerospace and space engineering applications. Abstract: Shape memory polymers and their composites are capable to hold a temporary shape and recover to the original shape upon exposure to a particular external stimulus. The stimulus light is considered as the optical radiation of any wavelength from 1 to 10 6 nm. Light enables unique and advanced shape memory effects that can fulfill the sophisticated demands in micro and small-scale engineering, biomedical, space and large-scale engineering applications. The ability to vary the stimulus light's wavelength, intensity, irradiated position, periodicity and polarization enables the progressions of wavelength selective, sequential, reversible and multiple shape memory effects. Current study provides a comprehensive review of the advances in experimental and numerical investigations on light activated shape memory polymers and composites. Actuation mechanisms, functionalities, characteristics, applications, merits and demerits of photoresponsive shape memory polymers and photothermal shape memory polymer composites are considered. The recent advancements on material design and optical technologies have dramatically changed the light activation scenarios of shape memory polymers. Advanced optical technologies and light dispersion methods that are advantageous for the light activation of SMPs are described. However, to date there are many unexplored areas that need to be researched further to develop sophisticated real-life applications of light activated shape memory polymers and composites. Herein the future research opportunities and directions are highlighted.